The Effect of Ferula Assafoetida Hanging on the Morphometric Changes of the Reproductive Organs of the Rocks (Eurasian Research Bulletin, 2022)
In this article, the morphometric changes of the reproductive organs in the postnatal ontogeny of Karakol cows under the influence of Ferula assafoetida fertility are presented